A Configurational Perspective on the Theory of Planned Behaviour to Understand Employees' Change‐Supportive Intentions. Issue 1 (16th November 2017) - Straatmann, Tammo; Rothenhöfer, Lisa Maria; Meier, Alexander; Mueller, Karsten
Abstract : This study aims to deepen the understanding of the psychological processes involved in the formation of change‐supportive intentions by adopting a configurational perspective. To investigate potential configurations in relevant psychological processes suggested by the theory of planned behaviour (Ajzen, 1991 ), classical linear analytic methods are supplemented by the application of two case‐centred methods: latent profile analysis (LPA) and fuzzy set qualitative comparative analysis (fsQCA). The study uses data from two measurement times drawing on employees of a city council ( t 1: N = 1, 589; t 2: N = 1, 524) undergoing complex and continuous organisational changes. While the case‐centred results from LPA and fsQCA generally accord well with the results from regression analysis, they consistently highlight the relevance of configurational patterns. Specifically, LPA and fsQCA reveal that different combinations of change‐related attitudes, subjective norms, and perceived behavioural control relate to the presence or absence of high supportive intentions. These results provide valuable insights for fostering employees' change‐supportive intentions. Moreover, the present study demonstrates that case‐centred analytical methods can essentially enrich research and theory‐building in change management as well as in the field of behavioural intention formation in general.